Detection of florfenicol resistance in opportunistic Acinetobacter spp. infections in rural Thailand - Tan, Bernice Siu Yan; Mohan, Lalit; Watthanaworawit, Wanitda; Ngamprasertchai, Thundon; Nosten, Francois H.; Ling, Clare; Bifani, Pablo (Frontiers in Microbiology, 2024)
Florfenicol (Ff) is an antimicrobial agent belonging to the class amphenicol used for the treatment of bacterial infections in livestock, poultry, and aquaculture (animal farming). It inhibits protein synthesis. Ff is an analog of chloramphenicol, an amphenicol compound on the WHO essential medicine list that is used for the treatment of human infections. Due to the extensive usage of Ff in animal farming, zoonotic pathogens have developed resistance to this antimicrobial agent. There are numerous reports of resistance genes from organisms infecting or colonizing animals found in human pathogens, suggesting a possible exchange of genetic materials. One of these genes is floR, a gene that encodes for an efflux pump that removes Ff from bacterial cells, conferring resistance against amphenicol, and is often associated with mobile genetic elements and other resistant determinants. In this study, we analyzed bacterial isolates recovered in rural Thailand from patients and environmental samples collected for disease monitoring. Whole genome sequencing was carried out for all the samples collected. Speciation and genome annotation was performed revealing the presence of the floR gene in the bacterial genome. The minimum inhibitory concentration (MIC) was determined for Ff and chloramphenicol. Chromosomal and phylogenetic analyses were performed to investigate the acquisition pattern of the floR gene. The presence of a conserved floR gene in unrelated Acinetobacter spp. isolated from human bacterial infections and environmental samples was observed, suggesting multiple and independent inter-species genetic exchange of drug-resistant determinants. The floR was found to be in the variable region containing various mobile genetic elements and other antibiotic resistance determinants; however, no evidence of HGT could be found. The floR gene identified in this study is chromosomal for all isolates. The study highlights a plausible impact of antimicrobials used in veterinary settings on human health. Ff shares cross-resistance with chloramphenicol, which is still in use in several countries. Furthermore, by selecting for floR-resistance genes, we may be selecting for and facilitating the zoonotic and reverse zoonotic exchange of other flanking resistance markers between human and animal pathogens or commensals with detrimental public health consequences.